Temporary Easement Valuation for Construction Site - Too, Kai Sheng; Kasim, Rozilah (Research in Management of Technology and Business, 2022)
A temporary construction easement is necessary when construction activities require other lands for access roads. Previous studies related to temporary easement are rare and very little guidance and references to the practitioners during the process of valuation. Even though, the legal statutes and law cases provide some guidance but that is not enough for evaluating temporary easement. The purpose of this research is to identify the factors that affect the temporary easement and to define the process of temporary easement valuation. This research applied the embedded qualitative and single case design as the research strategy. Semi-structured interviews were conducted with the public valuers and land administrators. The data were analysed using thematic analysis. Research findings identified factors that affect the temporary easement valuation and defined the process of the temporary easement valuation. The results have benefited the valuation practitioners, land administrators and constructors.